The effects of Leventhal’s self-regulation model-based educational intervention on stress, anxiety, and depression in women with multiple sclerosis: a randomized educational trial - Mahsa Hosseini; Soheila Shamsikhani; Ali Jadidi; Fatemeh Rafiei (Frontiers in Neurology)
BackgroundMultiple sclerosis (MS) is a long-term, progressive neurological condition that affects the myelin sheath of nerve cells in the central nervous system. Mental health concerns are often overlooked in individuals with MS, stemming from various aspects of the illness, such as its inherent characteristics and symptoms. The present research aimed to examine the impact of Leventhal self-regulation training on stress, anxiety, and depression in MS patients.MethodsThe current study was conducted as a randomized educational trial of 60 women referred to the MS Association in Arak City in 2024. The study implemented self-regulation training via the Leventhal model, which consisted of an initial face-to-face session to provide basic knowledge, eight offline sessions, and two online group sessions. The data were input into SPSS 26 software. Chi-square tests and Fisher’s exact tests were utilized, independent t-tests, and Mann–Whitney’s nonparametric equivalent. A repeated measures analysis of variance was conducted to assess the changes over three time points. Additionally, the Bonferroni post hoc correction was utilized. In the present study, data collection consisted of two parts: the demographic information form and the Depression Anxiety Stress Scale (DASS) questionnaire. The Iranian registry Clinical Trial code (IRCT) is IRCT20220703055351N3.ResultThe findings of this research indicated that there were no disparities in anxiety (p = 0.072), stress (p = 0.067), or depression (p = 0.170) between the control and experimental groups before the intervention. The mean (± standard deviation) anxiety, stress, and depression scores of the experimental group changed from 4.89 (4.34), 8.55 (5.57), and 6.82 (4.26) to 1.96 (2.48), 4.93 (4.55), and 4.37 (3.73) after the intervention, respectively (p < 0.05).DiscussionRecent research has shown that training based on the Leventhal model is effective in reducing stress, anxiety, and depression in MS patients. Additionally, the results showed that the ability of Leventhal training to improve depression was stable for one month.Clinical trial registrationhttps://irct.behdasht.gov.ir/, IRCT20220703055351N3.